A Century of Macroeconomics: From Keynes to the Present - Wimalaratana, W. (Department of Economics, University of Colombo, Sri Lanka., 2025)
This paper charts the evolution of macroeconomic thought, tracing its development from classical economics, with emphasis on market efficiency and limited government, to contemporary theories. It examines the Keynesian revolution, springing from the Great Depression, which underscored the importance of aggregate demand and active government intervention for economic stabilization. The subsequent rise of monetarism, challenging Keynesianism by prioritizing monetary policy in inflation control is analyzed. The paper then explores New Classical economics, focusing on rational expectations and market clearing, and its progression into New Keynesian economics, which integrates microeconomic foundations and acknowledges price and wage rigidities. Key macroeconomic branches such as economic growth, business cycles, labor economics, monetary and fiscal policy, and international economics are discussed, alongside the emerging field of behavioral macroeconomics. The influence of international institutions like the IMF and World Bank on financial stability, economic development, and global policy coordination is also highlighted. Current debates surrounding financial markets, inequality, and long-term growth are examined, emphasizing the increasing reliance on empirical evidence. Finally, the paper addresses future challenges including climate change, globalization, technological advancements, and cryptocurrencies, noting emerging research trends like big data, machine learning, and network analysis, concluding with a call for ongoing dialogue to address 21st-century economic complexities.
Keywords: Macroeconomics; Economic Thought; Keynesianism; Monetarism; New Classical; Policy Implications